Calcium Carbonate Mineralization in a Surface-Tension-Confined Droplets Array - Zhong He; Zengzilu Xia; Mengying Zhang; Jinbo Wu; Weijia Wen (Crystals, 2019)
Calcium carbonate biomimetic crystallization remains a topic of interest with respect to biomineralization areas in recent research. It is not easy to conduct high-throughput experiments with only a few macromolecule reagents using conventional experimental methods. However, the emergence of microdroplet array technology provides the possibility to solve these issues efficiently. In this article, surface-tension-confined droplet arrays were used to fabricate calcium carbonate. It was found that calcium carbonate crystallization can be conducted in surface-tension-confined droplets. Defects were found on the surface of some crystals, which were caused by liquid flow inside the droplet and the rapid drop in droplet height during the evaporation. The diameter and number of crystals were related to the droplet diameter. Polyacrylic acid (PAA), added as a modified organic molecule control, changed the CaCO3 morphology from calcite to vaterite. The material products of the above experiments were compared with bulk-synthesized calcium carbonate by scanning electron microscopy (SEM), Raman spectroscopy and other characterization methods. Our work proves the possibility of performing biomimetic crystallization and biomineralization experiments on surface-tension-confined microdroplet arrays.